Naming Outcome After Left or Right Temporal Lobectomy in Patients with Bilateral Language Representation by Wada Testing - Janecek, Julie K. (2013)
OBJECTIVE: To examine language outcome after left or right anterior temporal lobectomy (ATL) in epilepsy patients with bilateral language representation on intracarotid sodium amobarbital (Wada) testing. METHODS: Twenty-two epilepsy patients with bilateral language (Wada laterality index between −50 and 50) underwent right ATL (RATL, n = 10) or left ATL (LATL, n = 12). All patients were administered the Boston Naming Test pre-operatively and six months post-operatively. RESULTS: LATL patients showed greater post-operative naming decline than RATL patients. Group differences were also observed on subtests of the Wada test. Performance on the Wada naming and comprehension subtests was better in the non-surgical hemisphere than the surgical hemisphere in the RATL group, but there was no difference between the non-surgical and surgical hemisphere naming and comprehension performance in the LATL group. CONCLUSIONS: LATL patients with bilateral language are at greater risk for naming decline than RATL patients with bilateral language. This difference may be due to relatively better naming and comprehension abilities in the nonsurgical hemisphere in the RATL group.